Non-suppression of cortisol secretion by long term treatment with ketoconazole in patients with acute leukaemia. Issue 6 (June 1985) - Dandona, P; Mohiuddin, J; Prentice, H G
Abstract : Ketoconazole, a potent antifungal agent, inhibits adrenal steroidogenesis in normal subjects during short term treatment. Since this drug is used in the long term prophylaxis of fungal infections in patients with haematological malignancies, we have investigated whether such patients have evidence of adrenocortical suppression. Six patients on long term prophylaxis with ketoconazole were given tetracosactrin stimulation tests. All patients had high basal cortisol concentrations, which increased further after administration of 25 IU of tetracosactrin. It is concluded that leukaemic patients receiving long term ketoconazole treatment do not have adrenocortical suppression. They may, in fact, have hyperstimulated adrenocortical function due to stress and hypovolaemia.